Fatalities Due to Indigenous and Exotic Species in Florida1. Issue 1 (23rd August 2013) - Wolf, Barbara C.; Harding, Brett E.
Abstract Florida's climate is suitable for many potentially hazardous animals, including both indigenous and exotic species, which are frequently kept as in zoos or as pets. This has resulted in many unforeseen fatal encounters between animals and the ever expanding human population. While the literature and knowledge pool for more common types of deaths referred to medical examiner/coroner's offices is abundant, the appreciation of wildlife and exotic pet‐related deaths is far less widespread. We report seven animal attack‐related deaths that occurred in Florida. The inflicted injuries included blunt and sharp force injuries, asphyxia, drowning, and envenomation. The underlying cause of death, however, was always a result of the human/animal interaction and in many cases related to human error and failure to appreciate the potentially dangerous behavior of nondomesticated species. These cases illustrate the varied circumstances and pathophysiologies associated with deaths due to indigenous and exotic species and the importance of the multidisciplinary approach in the medicolegal investigation of these cases.